Blood Coagulation Studies and Extracorporeal Circulation in Man - Thurnherr, N (Thrombosis and Haemostasis, 1967)
Blood clotting investigations have been executed in 25 patients who have undergone open heart surgery with extracorporeal circulation. A description of alterations in the activity of blood clotting factors, the fibrinolytic system, prothrombin consumption and platelets during several phases of the operation is given.